Exploring the Impact of Age and Proficiency: English Word Stress Placement in Indonesian EFL Learners - Yanuar, Ivo Dinasta (English Education: Jurnal Tadris Bahasa Inggris, 2023)
The use of stress is perceived as the most influence factor in communication. The reason is not merely aware on the stress rule in a language but more on how to avoid the conflict of misunderstanding among the speakers. When every language has different rule on stress placement such as Indonesian language and English, this researh is inspired to conduct the investigation on the awareness and the use of English stress on Indonesian students in Cirebon, Indonesia. There are 14 selected English words which is loan in Indonesian vocabularies. It will help to know whether the participants can differentiate both tones and stress in the test. The result of this study shows the age and English competence of Indonesian students influences the accuracy of English word stress placement. The implication of this research is to build an awareness on English teaching learning on young learners.